Preparation of well-dispersed and anti-oxidized Ni nanoparticles using polyamioloamine dendrimers as templates and their catalytic activity in the hydrogenation of p-nitrophenol to p-aminophenol - Ma, Zhenye; Wu, Rujun; Han, Qiaorong; Chen, Rizhi; Gu, Zhenggui (The Korean journal of chemical engineering, 2011)
p -Aminophenol was synthesized by catalytic hydrogenation of p -nitrophenol on Ni nanoparticles prepared by a chemical reduction method using polyamidoamine (PAMAM) dendrimers as templates. The as-prepared Ni nanoparticles were characterized by XRD, LRS, EDS, FTIR, FESEM, HRTEM and N 2 sorption analysis. Smaller-sized, better-dispersed and more active Ni nanoparticles can be successfully achieved using PAMAM dendrimers as templates. Analysis results show the as-prepared Ni nanoparticles are pure f.c.c. nickel. In hydrogenation reactions of p -nitrophenol, Ni nanoparticles show higher catalytic activity than that of Ni nanoparticles prepared in the absence of PAMAM dendrimers. The weight ratio of PAMAM/Ni 2+ is proved to be an important parameter on the catalytic activity of Ni nanoparticles and the optimal ratio is 15%. The reason proposed for higher catalytic activity of Ni nanoparticles is a combination effect of smaller particle size, better dispersion and more active Ni nanoparticles.